Discovery of tetrahydroindazoles as a novel class of potent and in vivo efficacious gamma secretase modulators. Issue 12 (23rd July 2018) - Gerlach, Kai; Hobson, Scott; Eickmeier, Christian; Groß, Ulrike; Braun, Clemens; Sieger, Peter; Garneau, Michel; Hoerer, Stefan; Heine, Niklas
Graphical abstract: Abstract: The identification and optimization of a novel series of centrally efficacious gamma secretase modulators (GSMs) offering an alternative to the privileged aryl imidazole motif is described. Chiral bicyclic tetrahydroindazolyl amine substituted triazolopyridines were identified as structurally distinct novel series of GSMs. Representative compound BI-1408 ( (R) -42 ) was demonstrated to be centrally efficacious in rats at a 30 mg/kg oral dose.